2011
DOI: 10.1186/1471-2431-11-111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a vitamin/mineral supplement on children and adults with autism

Abstract: BackgroundVitamin/mineral supplements are among the most commonly used treatments for autism, but the research on their use for treating autism has been limited.MethodThis study is a randomized, double-blind, placebo-controlled three month vitamin/mineral treatment study. The study involved 141 children and adults with autism, and pre and post symptoms of autism were assessed. None of the participants had taken a vitamin/mineral supplement in the two months prior to the start of the study. For a subset of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
201
1
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(218 citation statements)
references
References 39 publications
4
201
1
12
Order By: Relevance
“…A placebocontrolled study involving 141 children with ASD demonstrated improvements in several sulfurrelated biomarkers, including total sulfate, adenosylmethionine, GSH, GSSG:GSH ratio, and taurine, following a vitamin/mineral supplement treatment program that specifically included methylsulfonylmethane (MSM) as a sulfur source [212], supporting the concept of sulfur deficiency in association with ASD. Cholesterol supplementation has been shown to improve symptoms such as irritability, hyperactivity, and sleep disorders in some children with ASD [213].…”
Section: Discussionmentioning
confidence: 99%
“…A placebocontrolled study involving 141 children with ASD demonstrated improvements in several sulfurrelated biomarkers, including total sulfate, adenosylmethionine, GSH, GSSG:GSH ratio, and taurine, following a vitamin/mineral supplement treatment program that specifically included methylsulfonylmethane (MSM) as a sulfur source [212], supporting the concept of sulfur deficiency in association with ASD. Cholesterol supplementation has been shown to improve symptoms such as irritability, hyperactivity, and sleep disorders in some children with ASD [213].…”
Section: Discussionmentioning
confidence: 99%
“…This can relate to the findings of Adams et al [20] which showed that nutritional and metabolic status of children with autism can be improved by supplements of oral vitamin/mineral, whereby the dose was increased during the first 3 weeks, suggesting that these supplements should be taken into consideration as a complementary therapy. Likewise, it has been observed that Vitamin C can decrease stereotyped behaviors in children with ASD [14].…”
Section: Nutraceuticalsmentioning
confidence: 98%
“…Lower levels of plasma ATP and red blood cell NADH were reported in children with autism than in controls. Vitamin and minerals supplements were associated with greater significant improvement in ATP and NADH levels as well as subscores on the hyperactivity, tantrum, and receptive language in the autism group compared with the placebo group [134][135]. In addition, gene variants of the NADH-ubiquinone oxidoreductase 1α subcomplex 5 (NDUFA5), an enzyme complex in the mitochondrial electron transport chain, are associated with autism [136].…”
Section: Oxidative Stressmentioning
confidence: 99%